Profitability and Socioeconomic Characteristics of Fish Production in Anambra State, Nigeria - Beatrice, Onyekachukwu Ifeoma; Gabriel, Oche Sunday; Dahutu, David I.; Peace, Gambo H.; David, Bando Christopher (Darul Yasin Al Sys, 2024)
In recent decades the impact of agriculture towards achieving a sustainable economy in Nigeria cannot be under emphasized, though, in time past it has been a subject of several debates amongst development economists, food security and stability is key to the developmental economy of any nation thus, the need to investigate fish production and management in Abia state. Three (3) zone comprising of Awka zone, Onitsha zone and Aguata zone were investigated with a pooled sample inclusive as standard and the analysis was based on the following parameters: Socio-economic Characteristics of Fish farmers, Systems of Fish Production, Management and the Level of Fish Production Associated with the Fish Management Systems, Price of Fish and Net Return from Fish Production. The result obtained showed that fish farming is practiced by both male and female with 96.67% and 3.33% respectively; majority (24.17%) of the fish farmers are within the age bracket of 51-55 years, while 23.33%, 22.50%, 17.50%, 11.67% and 0.83% of the farmers are within the age brackets of 41-45, 51-60, 46-50, 36-40 and 31-35 years respectively; 100.00% of the farmers had basic formal education with an average of 6 years farming experience; 67.50% purchased the fingerlings stock, while 32.50% of them hatched their fingerlings; 60.00% of the farmers produce heterobranchus, 27.50% of them produced heterobranchus and clarias, while 12.50% of the farmers produced heterobranchus and tilapia; 12.50% of the farmers were below 40 years of age, signifying the need to empower and encourage the youth to go into fish farming. the mean output of a fish farmer per year in Awka, Onitsha and Aguata Zones are 3.88 tonnes, 3.81 tonnes and 3.35 tonnes of fish respectively with grand mean output of 3.71 tonnes in Anambra state. Since there is need to increase protein intake level of people of the state and nation in general, fish production has to be developed and all the constraints militating against its effective production be checked so as to meet up with the protein need of the people.